Becoming an Engaged Dance Scholar Through Arts-Based Community Engagement Projects - Lynnette Young Overby; Diana Crum; Jill Grundstrom; Francine E. Ott; Melissa van Wijk (Center for Educational Policy Studies Journal)
Postgraduate dance education students can develop a practice of arts-based, engaged scholarship by applying their disciplinary knowledge in collaboration with community partners to enact projects that benefit local, regional and/or global communities and their own scholarship. The present article analyses seven arts-based research projects required as part of the Studio Seminar course for doctoral dance education students at Teachers College, Columbia University. The specific goals of the research project were (a) to assess the level of community engagement present in seven Studio Seminar projects, (b) to determine whether or not the criteria of “evocation and illumination” were fulfilled in the Studio Seminar projects, and (c) to determine the knowledge gained by the participating students who conducted and reflected upon the Studio Seminar projects. Two cohorts of students participated in the study: Cohort 1 (three participants), who completed the course in 2021, and Cohort 3 (four participants), who completed the course in 2023. The data were collected and analysed based on the arts-based research evaluation criteria of evocation and illumination, and the community engagement criteria of co-creation, co-implementation, co-assessment and co-dissemination. The results of this exploratory study reveal that the community engagement criteria of co-creation, co-implementation and co-assessment were present in all of the projects, but co-dissemination was only possible for the students who completed their projects in the first cohort. In addition, the arts-based research criteria of evocation and illumination were present in all seven projects. Furthermore, the results of a Community Engagement Questionnaire revealed that the projects had a positive impact on the students’ dissertation goals and their plans for future community engagement projects. In conclusion, providing postgraduate dance education students with guidance in developing arts-based, community-engaged projects assists in their development as engaged scholars.